AROMATHERAPY ADMINISTRATION AND PAIN SCALE 24 HOURS POST-CAESAREAN SECTION - Herlyssa; Theresia EVK (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
Aromatherapy can be used to reduce post-sectio caesaria (SC) pain. In this study, the aromatherapy used was orange essential oil. This quasi-experimental study used a pre and posttest design with control group. The sample of the study was 74 mothers with 24 hours post-SC. The treatment group was the mothers who were given orange essential oil aromatherapy (37 people), while the control group was those who were not given (37 people). Sampling technique used consecutive sampling. Data collection about the characteristics of the respondents was done using a questionnaire, while the measurement of pain was carried out using the Numerical Rating Scale (NRS) observation sheet. The analysis consisted of bivariate analysis with Wilcoxon test. There was a decrease in the pain scale in the treatment group after being given aromatherapy essential oil orange from 4.14 ± 1.669 to 2.59 ± 1.334 (p-value = 0.000). In the control group, the change was from 2.86 ± 0.419 to 2.78 ± 0.479 (p-value = 0.373). This meant that the treatment group showed higher reduced pain than the control group. Therefore, orange essential oil aromatherapy was effective in reducing pain scale 24 hours post-SC.